Mapping Research Themes and Trends in Ergonomics within Industry 5.0: A Bibliometric Analysis - Cahyawati, Amanda Nur; Sari, Sylvie Indah Kartika; Putro, Wisnu Wijayanto; Lina Dianati Fathimahhayati, (International Journal of Scientific Research and Management (IJSRM), 2024)
Abstract:Industry 5.0, the next stage of development after Industry 4.0, centers around the seamless integration of individuals and technology inside industrial processes to foster innovation that prioritizes human needs and experiences. Industry 5.0 diverges from Industry 4.0 by placing greater emphasis on the collaborative partnership between humans and machines rather than solely focusing on automation and advanced technologies like IoT and AI. The study employs bibliometric analysis to delineate the subjects and research areas in ergonomics within the context of Industry 5.0. The study analyzed literature from the Scopus database to identify trends and gaps in implementing ergonomic principles across different industrial sectors. The study addresses two distinct research inquiries: identifying overarching research subjects and emerging research themes. The results indicate the existence of four primary research clusters: the interaction between humans and advanced technology, the safety of work and collaboration between humans and robots, the optimization of multiple purposes and sustainable development, and the application of augmented reality in industrial design. The report emphasizes the growing importance of human-robot collaboration and artificial intelligence while acknowledging a decline in emphasis on user experience and virtual reality. The findings thoroughly analyze the present condition and development of ergonomics research in Industry 5.0 while providing significant recommendations for future investigations and real-world implementations.